ANALISIS PEMASARAN JERUK KEPROK DI KINTAMANI, BANGLI - Ni Wayan Sulastini; Made Tamba; I Made Budiasa; I Gusti Ayu Diah Yuniti (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2022)
This research is entitled Marketing Analysis of Tangerines in Kintamani, Bangli. The purpose of this study was to analyze costs, profits and margins as well as marketing channels for tangerines. Determination of the number of samples for tangerine consumers was carried out using a simple random sampling method with the slovin formula in which the sample size was 35 farmers and 17 people in marketing institutions with snowball sampling, consisting of 5 collectors traders, 5 retailers and 7 consumers. The results of the research show that in the first-level marketing channel, producers sell their products directly to consumers, in the second-level marketing channel, farmers to collectors and then to consumers, and in the third-level marketing channel, producers to collectors to retailers and then to consumers. The marketing cost obtained in channel I was Rp.250/kg, in channel II was Rp.550/kg, and in channel III was Rp.1,200/kg. While the marketing margin obtained in channel I is Rp.0/kg, in channel II is Rp.1000/kg at the collector level and Rp.1000 at the consumer. While the marketing margin obtained in channel III is Rp. 1000/kg at the collector level, Rp. 1,000 at the retail level, and Rp. 2,000 at the consumer level. The profit margin on marketing channel I is Rp.0, channel II at the collector level is Rp.450, and Rp.450 at the consumer level. while the profit margin on channel III is at the collector level, Rp. 450 at the retail level, and Rp. 6,200 at the consumer level.